1961
DOI: 10.1515/znb-1961-0108
|View full text |Cite
|
Sign up to set email alerts
|

Über die Wirkung von β-Strahlen auf die Photosynthese-Phosphorylierung und die Hill-Reaktion isolierter Chloroplasten

Abstract: Isolated spinach chloroplasts were exposed to ionising radiation (β-rays) from 90Sr. After irradiation photosynthetic-phosphorylation (PP) and Hill - reaction (HR) were checked and found to have high, but markedly different resistance. Dosis effect-curves were found indicating fifty percent inactivation of 130 000 rad (PP) or 530 000 rad (HR) respectively. There was no special effect of temperature on radiation resistance of the susceptible photosynthetic-phosphorylation. Results are discussed regarding their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1962
1962
1967
1967

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Investigators of the action of ionizing radiation on photosynthetic processes in isolated chloroplasts have observed that the phosphorylation reactions are more sensitive than the electron transport and the O2-evolving system (4,7,13). Simonis and Urbach (19) obtained similar restults in v vo using A ukistrodesmuiiis.…”
mentioning
confidence: 90%
“…Investigators of the action of ionizing radiation on photosynthetic processes in isolated chloroplasts have observed that the phosphorylation reactions are more sensitive than the electron transport and the O2-evolving system (4,7,13). Simonis and Urbach (19) obtained similar restults in v vo using A ukistrodesmuiiis.…”
mentioning
confidence: 90%